Influence of Pipe-Wall Parameters on Non-Intrusive Planar Capacitive Spatial Filter for Solids Flow Measurement - Al-Shalchi, Abbas Ahmed; Al-Khesbak, Mohammed Sahib (Nahrain University College of Engineering Journal, 2014)
The paper proposes installing a planar capacitive spatial filter (PCSF)behind thin walls of a dielectric pipe section to operate as a non-invasive sensor for solids flow measurement. The pipe wall shields the electrodes from erosion caused by solid particle flow.A computational model of the flow sensorincorporating the shielding layer is developed. The model’s equations are solved using finite difference and relaxation methods and it is then used to examine the effects of the thickness and dielectric constant of the shield on the amplitude and shape of the flow signals. The results show thatmaking the ratio of the shield thickness to the substrate thickness near to the reciprocal of their respective dielectric constants gives asatisfactory combination ofenhancement of sensor sensitivityandobtaining flow signals of smoother shape.